Financial Market Risk and U.S. Money Demand - Cook, David; Choi, Woon. (Washington, D.C. : International Monetary Fund, 2007)
This paper examines empirically U.S. broad money demand emphasizing the role of financial market risk. We find that money demand rises with the liquidity risk of stock markets or the credit risk of corporate bond markets. After controlling for the effect of financial market risk, money demand becomes relatively stable over the last 35 years. At the sectoral level, household money holdings continue to be stable in a traditional model controlling for a decline in transactions costs for investing in mutual funds in the early 1990s. In contrast, business money holdings have been consistently (positively) associated with credit risk.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet